Development of a 10-kV regional compensation dynamic voltage restorer with multiple functions. Issue 8 (3rd August 2019) - Jian, Le; Qian, Zhou; Cao, Wang; Huaying, Zhang; Senjing, Yao; Junwei, Cao
ABSTRACT: The first 10-kV regional compensation dynamic voltage restorer (DVR) has been installed in a 110-kV substation in Shenzhen power grid, to protect plenty of sensitive loads in a wide area simultaneously from the disturbances caused by voltage sags. The location selection and performance indicators of the DVR are determined based on the voltage sag statistic results in recent years of Shenzhen power grid. The implementation schemes of main circuit elements, such as the energy storage unit, inverter and LC filter are presented. To further improve the DVR's cost-effectiveness, a novel virtual impedance control strategy is proposed to provide the DVR with a function of a Fault Current Limiter (FCL) or a Series Compensator (SC) besides the function of voltage sag compensation. Simulation and field experimental results are provided to show the correctness and effectiveness of the main circuit design and control system development of the 10-kV DVR.